2023
DOI: 10.5424/fs/2023321-18932
|View full text |Cite
|
Sign up to set email alerts
|

Carbon storage in tree biomass dispersed in pastures in the arid Caribbean region of Colombia

Abstract: Aim of study: To determine the importance in terms of carbon sequestration of dispersed trees in pasture lands as a greenhouse gas (GHG) mitigation measure. Area of study: The study was carried out in the municipality of Agustin Codazzi (Cesar Department, Colombia), between October 2020 and March 2021. Material and methods: We characterized 43.57 hectares dispersed amongst sixteen plots and all trees with a diameter at breast height > 10 cm were measured. Allometric equations were used to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This means that the greater the diversity of species, the greater the carbon store [9,52]. Furthermore, several studies affirm that the transition from monocultures to AFSs has a great potential to store carbon, which improves with the age and density of tree species [34,52], such as silvopastoral systems (SPSs) in the arid region of Colombia with 7.15 Mg C ha −1 [1] and other studies in Colombian territory (31 Mg C ha −1 ) [56]. In this context, it is confirmed that SPSs and AFSs are important management and improvement alternatives to counteract the expansion of the agricultural frontier and therefore minimize GHG emissions that lead to global warming.…”
Section: Stored Biomass Carbonmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that the greater the diversity of species, the greater the carbon store [9,52]. Furthermore, several studies affirm that the transition from monocultures to AFSs has a great potential to store carbon, which improves with the age and density of tree species [34,52], such as silvopastoral systems (SPSs) in the arid region of Colombia with 7.15 Mg C ha −1 [1] and other studies in Colombian territory (31 Mg C ha −1 ) [56]. In this context, it is confirmed that SPSs and AFSs are important management and improvement alternatives to counteract the expansion of the agricultural frontier and therefore minimize GHG emissions that lead to global warming.…”
Section: Stored Biomass Carbonmentioning
confidence: 99%
“…Currently, tropical forests constitute 45% of the global forest area according to FAO 2020 [1]. However, in recent times there has been a significant decrease, due to the deforestation and degradation of tropical forests due to the constant change in land use [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation